Persepsi Guru dan Siswa Terhadap Proses Pembelajaran Tatap Muka Terbatas Pada Mata Pelajaran Biologi Di SMA Negeri 9 Pulau Taliabu - Kenta, Abd. Muin; Titdoy, Nadia; Nurlia, Nurlia (Jurnal Biologi Babasal, 2023)
Abstract: The limited offline learning during the pandemic COVID-19, of course has its own challenges due to the limitations of maintaining each other's health protocols for both teachers and students. The implementation of limited offline learning is expected to improve the quality of learning for teachers and students in the situation of the pandemic virus Covid-19. This research aims to determine (i) teachers' perceptions of offline learning are limited to biology subjects at SMA Negeri 9 Pulau Taliabu, (ii) teachers' perceptions of offline learning are limited to biology subjects at SMA Negeri 9 Pulau Taliabu. This research used qualitative descriptive research. The population in this study were biology teachers and students which consist of 72 of 1 biology teacher and 71 students. The number of samples was 1 biology teacher and 61 students. The data collection technique used in this research were interviewing that was done to the teacher and giving questionnaires to the students. The data were analyzed using a qualitative descriptive method. The results showed that (i) there were many obstacles faced by teachers which affected in the limited offline learning process that becomes not running effectively, therefore, teachers needed support from all parties in order to make the process of conducting limited offline learning could be carried out properly. (ii) The students' perception of the limited offline learning process to the biology subject were very good.